Reflection of Ideology: A Critical Discourse Analysis of Donald Trump’s Declaration Speech of Jerusalem as Capital City of Israel - Widyo Andana Pradiptha; Tuti Purwati; Chusni Hadiati (J-Lalite: Journal of English Studies, 2020)
This research focuses on the legitimacy of Donald Trump’s speech in declaring Jerusalem as the capital city of Israel on December 2017. This research aims to: (1) identify the text structure of the speech, (2) describe the social cognition of this speech, (3) and to reveal the social context of this speech. The compiled data is analyzed by using Van Dijk’s CDA theory of socio-cognitive (1988). This theory has interrelated three dimensions of analysis consisting of text structure, social cognition, and social context. The method of this research is qualitative by using the descriptive analysis. The data source of this research is the speech text of Donald Trump declaration speech of Jerusalem as Israel’s capital on December 2017. The result of this research shows that there is semantic aspect (microstructure) used by Donald Trump: Background (7), Detail (4), and Presupposition (15). From the analysis, the researcher argues that Donald Trump tends to be pro-Israel. This is supported in the structure of the text by how it consistently uses direct language to influence the emotional attachment of the intended by using logical facts and emotional involvement to make negative out-group representations to get positive representations to them and their allies. Furthermore, social cognition reveals the ideology and partisanship of Donald Trump about this conflict. It can be identified clearly by correlating the context of this speech to something that related to Israel-Palestine conflict. In social cognition, as the president of the United States of America, Donald Trump has a massive influence to the international world, even though it caused pros and contras for all elements of society. Possible further research about critical discourse analysis can be conducted by analyzing other issues. In short, it is also a suggestion to the other researchers to investigate more variation data such as news, advertisement, movie, and so on